An Economic Analysis of Blockchains - Patrick Waelbroeck (Center for Economic Studies and ifo Institute (CESifo), 2018)
The blockchain is a technology that goes beyond timestamping, bitcoin and secure financial transactions. The development of an ecosystem around smart connected objects will probably not happen without the blockchain (in one form or another). The blockchain opens the door to the liquification of the physical world, to the economy of real-time micro-transactions and to smart data sharing. However, it is necessary to distinguish between the different types of blockchains, especially between public and private blockchains, because their economic properties are contrasted. Moreover, governance issues in public blockchains seem to indicate that the technology alone cannot guarantee trust.
Keywords: E51; G34; H41; L14; L52; 330; blockchain; bitcoin; ether; security; payment; governance; trust; oracles; forks; hash; smart contracts; tokens; smart locks; technology diffusion; crypto-currency; financial privacy